Isolation of alkalophilic microorganism from local hot spring - Mohd Zulhilmi, Wan Salleh (2008)
Alkaline environments are typical extreme environments which include naturally occurring soda lakes, deserts, soils and artificially occurring industrialderived waters. Micro-organisms that occupy extreme pH environments have resulted in the definition of an unusual group, termed alkaliphiles. In this review, the current status of the biodiversity of alkaliphilic micro-organisms in hotspring environments and aspects of their biotechnological potential are summarized briefly. The sample was taken from the local hot spring which is Sungai Klah, Perak and the temperature at its condition was recorded. The sample was inoculated in alkaline medium or known as Hirokoshi medium and incubated for the growth of the culture. By using enrichment technique, sample from each culture were spread on selective agar plate. As a result, only alkalophilic microbes grow by using selective agar plate. Alkalophilic microorganism was characterized. In this experiment, morphology test has been done to determine its shape, size and arrangement. The microbe was characterized using simple staining, gram staining, spore staining and acid-fast staining. The results gave a microorganism with rod in shape, gram negative microbes, spore former and also non acid-fast cells Therefore, according to the morphology test, it was best described the alkalophilic microorganism that had been study is from Bacillus group.